Lemmus lemmus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Lemmus lemmus (Linnaeus, 1758). Syst. Nat., 10th ed., 1:59. TYPE LOCALITY: Sweden, Lappmark. DISTRIBUTION: Mountains of Scandinavia and tundra from Lapland to the White Sea (Corbet, 1978c; see Tast, 1982«, for European range). SYNONYMS: borealis, iretator, migratorius, norvegicus. COMMENTS: European populations reviewed by Tast (1982a). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 517, DOI: 10.5281/zenodo.7353098